Thanks COVID-19, I'll reconsider my purchase: Can fear appeal reduce online shopping cart abandonment? - Wang, Siqi; Cheah, Jun Hwa; Xin, Jean Lim; Leong, Yee Choy; Choo, Wei Chong (Elsevier, 2022)
Despite the widespread prevalence of online shopping cart abandonment (OSCA) and allusions to this behavior in popular press, scholars have yet to examine the key determinants of OSCA. This study used the stimulus-organism-response (S–O-R) model to explore the factors influencing consumers' OSCA and decision to buy from a land-based retailer. Two studies were carried out to test the proposed hypotheses among Mainland China's Generation Y consumers. Data was collected based on two product categories (i.e., apparel and electrical appliances) at two different time scenarios (i.e., pre- and post-pandemic). The findings reveal that hesitation at checkout increases OSCA, while consumers' decision to buy from a land-based retailer is influenced by their emotional ambivalence and OSCA. Furthermore, fear appeals appear to weaken the relationship between OSCA and the decision to buy from a land-based retailer. This study has implications for researchers and practitioners who seek to effectively reduce the rate of OSCA.